Sufi Tradition as Pre-Institutional Education in Kerinci: a Philosophical and Historical Analysis - ravico, ravico; Siregar, Anggi Desviana; Erniyati, Yelni; Fikri, Khirpal; Sustianingsih, Ira Miryani (POTENSIA: Jurnal Kependidikan Islam, 2026)
This study examines the role of Sufism as a pre-institutional Islamic education system in Kerinci, Sumatra, during the 19th and early 20th centuries. The main problem addressed is the historiographical tendency to focus on formal institutions such as pesantren and madrasah in coastal regions, while overlooking non-formal educational practices in peripheral highland areas like Kerinci. The research aims to investigate how Sufi tradition functioned as a systematic educational mechanism before the emergence of formal institutions in the mid-20th century. Employing a qualitative historical and philosophical approach, the study integrates three data collection techniques: philological analysis of twelve Arabic and Jawi manuscripts, in-depth semi-structured interviews with senior Islamic teachers and manuscript heirs, and documentary research on Dutch colonial records and local genealogies. Data analysis involved thematic coding, narrative construction, philosophical interpretation of Sufi concepts, and methodological triangulation to reconstruct the educational system. The findings demonstrate that Sufism, through zawiyah, majlis dzikir, ṭarīqah, and local manuscripts such as the Tarekat Manuscript (EAP117/21/1/1) and the Falakiyah Manuscript, effectively transmitted Islamic knowledge and values. These practices taught tawḥīd (monotheism), adab (ethics), and riyāḍah (spiritual discipline) via recitation, imitation, and spiritual apprenticeship. Philosophically, Sufi education emphasized tazkiyat al-nafs (soul purification) and holistic character formation. This research contributes to a deeper understanding of the plural trajectories of Islamic education in Indonesia. It highlights Sufism’s significant role in shaping the spiritual foundation, cultural identity, and Islamization process in Kerinci, while offering a model of flexible, relational, and contextually rooted pedagogy. The findings carry important implications for contemporary Islamic education by suggesting the integration of Sufi principles into modern systems, particularly in rural and peripheral communities.